Discrimination and Generalization of Negatively-Reinforced Mands in Young Children With Autism Spectrum Disorder. Issue 5 (September 2019) - Chezan, Laura C.; Drasgow, Erik; McWhorter, Gabriela Z.; Starkey, Kristine I. P.; Hurdle, Brooke M.
In this study, we extended the literature on the generalization of negatively-reinforced mands in three young children with autism spectrum disorder (ASD). First, we used example and nonexample stimuli embedded in mand training to teach a new, socially appropriate, negatively-reinforced mand to reject unpreferred food items while continuously assessing mand discrimination. Second, we evaluated the discriminated generalization of the newly acquired mand by using untrained example and nonexample stimuli. Finally, we conducted maintenance probes to examine if the new, discriminated mand occurred over time in the absence of training. Results suggest that our mand training produced acquisition of a discriminated negatively-reinforced mand in all three children. Data indicate that the newly acquired, discriminated mand generalized to untrained food items and was maintained after training was discontinued. We discuss the conceptual significance and clinical implications of using example and nonexample stimuli to produce acquisition, generalization, and maintenance of negatively-reinforced mands in young children with ASD and language delays.